2016
DOI: 10.1161/atvbaha.116.307626
|View full text |Cite
|
Sign up to set email alerts
|

Wnt2 and WISP-1/CCN4 Induce Intimal Thickening via Promotion of Smooth Muscle Cell Migration

Abstract: Objective-Increased vascular smooth muscle cell (VSMC) migration leads to intimal thickening which acts as a soil for atherosclersosis, as well as causing coronary artery restenosis after stenting and vein graft failure. Investigating factors involved in VSMC migration may enable us to reduce intimal thickening and improve patient outcomes. In this study, we determined whether Wnt proteins regulate VSMC migration and thereby intimal thickening. Approach and Results-Wnt2 mRNA and protein expression were specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…79 Wnt2 also induced WISP-1 expression in SMC in β-catenin-dependent manner. 80 Levels of Wnt2 and WISP-1 were elevated in ligated carotid arteries. Furthermore, WISP-1 overexpression promoted intimal thickening, which was reduced in Wnt2 +/− animals.…”
Section: Nowak Et Al Oxidative Stress and Atherosclerosis E45mentioning
confidence: 94%
See 2 more Smart Citations
“…79 Wnt2 also induced WISP-1 expression in SMC in β-catenin-dependent manner. 80 Levels of Wnt2 and WISP-1 were elevated in ligated carotid arteries. Furthermore, WISP-1 overexpression promoted intimal thickening, which was reduced in Wnt2 +/− animals.…”
Section: Nowak Et Al Oxidative Stress and Atherosclerosis E45mentioning
confidence: 94%
“…78 Wnt/β-catenin/WISP-1 (WNT1-induciblesignaling pathway protein 1) represents example of the pathway that can protect SMCs from apoptosis 79 and oxidative stress but, on the other hand, enhance SMC migration and contribute to intimal thickening. 80 Mill et al 79 showed recently that macrophage-derived Wnt5a could protect SMC from H 2 O 2 -induced apoptosis. Exogenous Wnt5a increased amounts of active and nuclear β-catenin in SMC and induced TCF (transcription factor) signaling.…”
Section: Nowak Et Al Oxidative Stress and Atherosclerosis E45mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Wnt signaling in ECs has been shown to activate proinflammatory gene expression via inhibition of canonical Wnt signaling and activation of the noncanonical Ca 2+ ‐dependent pathway via ligand Wnt5a 88, 89. Several studies have demonstrated a direct link between canonical Wnt signaling via ligands Wnt1, Wnt2, and Wnt3a and arterial smooth muscle cell proliferation, which underlies the intimal thickening stage of atherosclerosis 20, 21, 90, 91. Canonical Wnt signaling and LRP5 have also been directly implicated in the promotion of foam cell formation 6.…”
Section: Implication Of Wnt Signaling In Atherosclerosis Pathologicalmentioning
confidence: 99%
“…In addition to inhibiting Wnt3a-induced pancreatic beta-cell insulin secretion[68], Wnt4 stimulates VSM proliferation and promote arterial intimal thickening[69] as relevant to the cardiovascular disease of diabesity. Importantly, in very recent data, George and colleagues have identified matricellular proteins of the CCN family ( C ysteine-rich protein 61/ C onnective tissue growth factor/ N ephroblastoma overexpressed gene) as down-stream mediators of Wnt-initiated VSM migration during neointima formation[70, 71]. …”
Section: Introductionmentioning
confidence: 99%